Aplikasi Diagnosa Kebutaan Warna Menggunakan Metode Ishihara Untuk Android - Suryo Atmojo, Hardi; , Dr. Ir. Bana Handaga., M. T (2015)
One disorder that occurs in the eye is color blind. Color blindness is a condition in which a person can not distinguish certain colors that can be distinguished by people with normal eye. The development of Medical Science progress is color blind test using Ishihara book. Color Blind Test current is needed for the world of industry, education, and government. It is caused by human dependence in work or education closely related to color. Not only that, the use of paper that is easily torn and color fading when the long-unused makes testing no longer be perfect. For that reason the author makes the Color Blind Test applications that run on smartphone Android. Selection of the Android operating system because the operating system is open source. The author makes an application Color Blind Test this by referring to the book Dr. Shinobu Ishihara, so the rule is in use in accordance with the procedure.